Perbedaan Lama Pelepasan Plasenta dan Jumlah Perdarahan pada Ibu yang Melaksanakan dan Tidak Melaksanakan Inisiasi Menyusu Dini (IMD) - Bahiyatun Bahiyatun (Jurnal Riset Kesehatan, 2015)
This study aims to determine the time difference of detachment of the placenta and the amount of bleeding in women who carry out the Early Initiation of Breastfeeding (IMD) and those who donot. The design of the research is quasy experimental design. Whereas the methods used in this research is the Posttest Only Control Group Method. The results show that mothers who implement Early Initiation of Breastfeeding can deliver the placenta quicker.